Tetrahymena cilia cap is built in a multi-step process: a study by atomic force microscopy - Seixas, Cecília (2019)
In motile cilia, a basal body organizes the axoneme composed of nine microtubule doublets surrounding a central pair of singlet microtubules. The distal ends of axonemal microtubules are attached to the membrane by microtubule-capping structures. Since little is known about the early steps of cilium assembly, it was our aim to get insight into the first assembly stages and structure of motile cilia.